A statistical profile of Irish domestic tourism, 2000-2005 - MacFeely, S. (My University, 2007)
The 2000?2005 period was a turbulent one for the tourism industry. Yet despite shocks like September 11 and the outbreak of Foot and Mouth disease, domestic tourism has not only survived but also apparently thrived, with a nominal growth in trips and expenditure of 31% and 65% respectively. This paper attempts to put this increase in domestic tourism into perspective and examine some of the driving forces behind the growth, such as population, immigration, employment, income and price. The paper also highlights structural changes occurring on the supply side, such as the decline of the B&B sector and the emergence of holiday homes as an important sector. It also demonstrates the magnetic pull of the Greater Dublin Area on business tourism and highlights the differing tourism patterns associated with different age groups or whether children are involved or not. It is also argued that domestic tourism is less vulnerable to external shocks than inbound and outbound tourism and advocates that same day visits are perhaps far more important to domestic and national tourism than previously realised.
read before the Society, 1 March 2007
Keywords: Tourism; 314.15